DESIGN ENGINEERING DETAIL OF SONO (OPAK RIVER) MICROHYDRO IRRIGATION PROJECT PARANGTRITIS KRETEK VILLAGE IN THE DISTRICT OF BANTUL OF YOGYAKARTA - Arief Budiyanto (Master in Systems Engineering, 2015)
Bantul District has many small river which have the potency to be converted to electrical energy. This research aims at determination the potency of hydropower and designing very low head water power plant. The observational step started by measuring head and flow rate. Designing of water turbine should be considered the power available. Since the turbine usually run at low speed and the generator speed is quite high (1500 rpm) it require speed increaser. Based on primary data, the electrical power can be generated up to 41.02 kilowatt kW .The project’s objective is to provide the village Irrigation Sono (Opak river) Parangtritis with a reliable,green clean and economically viable source of electrical energy. A potential hydropower site in the vicinity of the villages was identified at Opak river. The salient features of the scheme are summarised as follows: Gross Head (Hgross) 2- 3.5 m , Net Head ( Hnett) 2.5 m, Flow River 4,48 m3 /s, Design of flow rate (Q) =2.5 m 3/s. Electrical Power (Pelg) 61,31 KW. The project comprises of the following components: Water intake and conveyance structures, including sand trap, headrace canal, forebay, draft tube and tailrace. Powerhouse, including protection wall Generating equipment, comprising of a propeller turbine and synchronous generator Electrical turbine control system, ELC (Electronic Load Controller) Transmission facilities.The implementation of the project will take approximately six to eight months including the finalisation of the preparatory work (detailed design, tendering, contract awarding), actual implementation of the project, testing, commissioning and training of operators. Two villagers will be assigned and trained as operators for the operation and maintenance of the plant. In order to optimize the viability of the water source office of Bantul, load management is deemed necessary to optimise the supply and demand situation, such as using energy pump for irrigation.